Using oligochaeta assemblages as an indicator of environmental changes - Behrend,RDL. (2012)
We designed a field survey (the entire river length; not dammed: First and Second plateaus; dammed: Third Plateau) to test the hypothesis that the cascade of reservoirs promoted a reduction in species richness and changed the composition of Oligochaeta assemblage along the Iguaçu River. Changes in environmental variables and in richness and composition of Oligochaeta were summarized by Canonic Correspondence Analysis. Along the Iguaçu River, conductivity, and altitude decreased, whereas temperature increased. Oligochaeta composition showed a significant spatial variation, with higher abundances of the family Tubificidae and the genus Dero (Naididae) occurring in the First Plateau. In the Second and Third plateaus, few species were dominant, with increases in the presence of species of Naididae below dams. We found a clear decrease in species richness along the Iguaçu River. Moreover, we found that Oligochaeta assemblage was influenced by some environmental variables such as altitude, conductivity, substrate type and temperature, and by anthropogenic activities (human occupation and damming). The results supported the use of Oligochaeta as surrogate taxa to predict environmental changes along impacted (dammed and eutrophic) rivers. The validity of this was indicated by the strong and significant gradient registered, from the headwater to mouth of the Iguaçu River.